1985
DOI: 10.1177/030098588502200605
|View full text |Cite
|
Sign up to set email alerts
|

Canine Laryngeal Rhabdomyoma

Abstract: Abstract. Three canine laryngeal tumors were diagnosed as oncocytomas by light microscopy, but were determined to be rhabdomyomas following ultrastructural and immunocytochemical examination. Tumors consisted of large eosinophilic cells interspersed with smaller dark cells. Large tumor cells had a granular, intensely eosinophilic cytoplasm. Scattered through the tumors were a few elongated cells with cytoplasmic cross striations and multiple nuclei. Tumor cells from all three dogs contained numerous mitochondr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
46
2

Year Published

2000
2000
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(49 citation statements)
references
References 13 publications
1
46
2
Order By: Relevance
“…In the dog, oncocytomas have been reported originally in the larynx and recently in the thyroid gland. 7,9,15 There is one report of a chromophilic-eosinophilic (oncocyte-like) renal cell carcinoma in a dog. 18 The authors described two different oncocyte-like populations of tumor cells and concluded from their morphologic and immunohistochemical studies that the tumor in that dog resembled a renal oncocytoma more than a renal carcinoma.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…In the dog, oncocytomas have been reported originally in the larynx and recently in the thyroid gland. 7,9,15 There is one report of a chromophilic-eosinophilic (oncocyte-like) renal cell carcinoma in a dog. 18 The authors described two different oncocyte-like populations of tumor cells and concluded from their morphologic and immunohistochemical studies that the tumor in that dog resembled a renal oncocytoma more than a renal carcinoma.…”
mentioning
confidence: 99%
“…3 Rhabdoid tumors ultrastructurally contain mitochondria and aggregates of myofilaments. [7][8][9] Specific immunohistochemical markers are helpful in making a differential diagnosis. Oncocytomas specifically express cytokeratin, 15,17 whereas renal cell carcinomas coexpress vimentin and cytokeratin.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The clinical presentation of a congenital subcutaneous mass with the histologic pattern described for this case are similar to the features seen in human FR and are distinctly different from the previous AR-like rhabdomyomas described in animals. 5,6,8 This is to our knowledge the first veterinary description of a 1) fetal rhabdomyoma and 2) an extracardiac congenital rhabdomyoma.…”
mentioning
confidence: 81%
“…The laryngeal neoplasms reported in dogs were rhabdomyomas, extramedullaryplasmacytomas, chondrosarcomas, carcinomas, fi brosarcomas and mastocytomas (MEUTEN et al, 1985;HAYES et al, 2007;MACPHAIL, 2014). Except for the rhabdomyomas, most of these neoplasms are locally invasive and have a high metastatic potential (WITHROW, 2013).…”
Section: Tumores De Laringe E Traqueia São Raros Em Animais De Estimamentioning
confidence: 99%